Pengaruh Kualitas Pelayanan terhadap Kepuasan Pelanggan dan Loyalitas Pelanggan (Studi Pada Bank BRI Unit Klojen Malang) - Adhita Larasati (Jurnal Ilmiah Mahasiswa FEB, 2018)
Abstract:  This  study  aims  to  determine  the  effect  of  service  quality  on  customer satisfaction and customer loyalty. This type of research is explanatory research which explains the causal relationship between the variables through hypothesis testing. This study used a sample of 250 respondents, the respondents were customers of BRI Klojen Unit Malang, aged more than or equal to 18 years. By using a non-probability sampling technique with a purposive sampling method. Direct hypothesis testing is done using a t- test. This analysis uses the Partial Least Square (PLS) test tool and is assisted by SmartPLS 3.0 software to facilitate research. The analysis results obtained in this study are  Assurance  has  a  significant  effect  on  customer  satisfaction,  Reliability  has  a significant effect on customer satisfaction, tangibles has a significant effect on customer satisfaction, Accessibility has a significant effect on customer satisfaction, and customer satisfaction  has  a  significant  effect  on  customer  loyalty.  These  results  indicate  that service quality has a significant effect on customer satisfaction and customer loyalty. Keywords: Assurance, Reliability, Tangibles, Accessibility, Customer Satisfaction, Customer Loyalty